Masyarakat Bantaran Sungai: Penggunaan Media untuk Kebutuhan Informasi - Atika; Achmad Bayu Chandrabuwono; Nadila (Institut Pertanian Bogor, 2023)
The media is one of the important elements in developing communication planning and strategy. The selection of the right media is one of the determining factors for the delivery of messages to the target, so it is necessary to know the ownership and access of media to certain communities. The objective of research was to analyze the use of media in riverbank communities in fulfill their information needs. The sample was 348 people with an error rate of 5%. The sampling technique used proportionate stratified random sampling to draw a sample based on the proportional population in each sub-district, chosen randomly. The results showed that the use of media to meet the information needs is still low in terms of frequency and duration of use. From many conventional media, the internet and social media, as well as short messages, television, and WhatsApp are the most frequent and longest used media compared to other media. The findings of this study can be a reference for communicators of health, environmental, economic, social, cultural, and other field programs in determining the right media, especially those that make riverbank communities their target audiences.